Digital Data Transmission Using Single-Sideband Modulation - Ouzas, Nicholas (My University, 1979)
The feasibility of using a partial response-encoded single-sideband (SSB) modulated signal for transmission of digital data in a radio system is considered. The principal methods of SSB signal generation and demodulation are examined, and the effects of carrier synchronization are determined. The effect of steady-state carrier phase errors on the error rate of an SSB partial response receiver is analyzed theoretically and by means of computer simulation. The analysis of a decision-directed SSB carrier phase tracking loop is presented and its performance is evaluated using computer simulation. The performance of the SSB partial response system after amplification by means of travelling-wave-tube (TWT) amplifiers is analyzed by using computer simulation. Finally, a comparison of an SSB partial response system and a quadrature partial response system (QPRS) is made.
Keywords: digital, data, transmission, single-sideband, modulation, synchronization